( g*-Pre Regular and g*-Pre Normal) –Cleavability - Ghazeel .Almahdi. Jalalah , Nazha Emhimed Alhaj (Journal of Pure & Applied Sciences, 2019)
D. Rayanagoudar and P. G. Patil [8] introduced two new classes of spaces, called g*-pre regular and g*-pre normal spaces.In this paper we studied the concept of cleavability over these spaces: (g*-Pre Regular and g*-Pre Normal) as following:1- If is a class of topological spaces with certain properties and if x is cleavable over p , then y E P2- If is a class of topological spaces with certain properties and if x is cleavable over p , then y E P